2012
DOI: 10.1089/scd.2011.0444
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Mesenchymal Stem Cells in Patients with Beta Thalassemia Major: Molecular Analysis with Attenuated Total Reflection-Fourier Transform Infrared Spectroscopy Study as a Novel Method

Abstract: Bone marrow mesenchymal stem cells (BM-MSCs) are the main cellular components of the bone marrow, providing a supportive cellular microenvironment to maintain healthy hematopoiesis. β-thalassemia major (β-TM) is characterized by anemia that is caused by a genetic defect in hemoglobin synthesis and results in ineffective erythropoiesis (IE). The alterations in the microenvironment in thalassemic bone marrow during IE can cause changes in BM-MSCs. This study aimed to investigate global structural and composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 62 publications
2
19
0
Order By: Relevance
“…MSCs of patients with NMHD were able to equally differentiate into osteoblasts and chondrocytes as MSCs of healthy donors. Similar results for MSCs of patients with thalassemia [29,30] and SCD [32,34] were reported. Interestingly, we observed that MSCs of all four tested patients with thalassemia differentiated less well into adipocytes than MSCs of other NMHD and control group.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…MSCs of patients with NMHD were able to equally differentiate into osteoblasts and chondrocytes as MSCs of healthy donors. Similar results for MSCs of patients with thalassemia [29,30] and SCD [32,34] were reported. Interestingly, we observed that MSCs of all four tested patients with thalassemia differentiated less well into adipocytes than MSCs of other NMHD and control group.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, MSCs of patients with thalassemia and SCD demonstrated an equivalent proliferation potential as MSCs of healthy donors as reported by several groups [32,34,35]. Only one group reported that thalassemic MSCs proliferate more than MSCs of healthy donors [30], in contrast to Crippa et al [31] who observed an opposite phenomenon. Flow cytometry analysis showed a significantly lower expression of CD146 antigen, as a more primitive cell marker, on MSCs of patients with TM, SCD and SCN compared to MSCs of healthy donors.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Samples were measured after hav-ing been dried on the crystal, similar to the method applied in the literature. 14,15 Briefly, fibroblast cell samples were mixed gently prior to the measurements to obtain homogeneity. 2.5 µL of cell suspension in PBS were spotted onto the ZnSe ATR crystal.…”
Section: Ftir Spectroscopy Data Collection and Evaluationmentioning
confidence: 99%